Protective effect of N-acetyl-L-cysteine against acrylamide-induced oxidative stress in rats - BECEREN, AYFER; ŞENER, GÖKSEL (SCIENTIFIC TECHNICAL RESEARCH COUNCIL TURKEY-TUBITAK, 2012)
Acrylamide (AA), used in many fields, from industrial manufacturing to laboratory work, is also formed during the heating process through the interactions of amino acids. Therefore, AA poses a significant risk for both human and animal health. This study aimed to elucidate whether N-acetyl-L-cysteine (NAC) treatment could modulate AA-induced oxidative changes in the brain, lung, liver, kidney, and testes tissues of the rat. Rats were divided into 4 groups, as the control (C), NAC [150 mg/kg intraperitoneally (i.p.)], AA (40 mg/kg i.p.), and NAC + AA groups. After 10 days, the rats were decapitated and the tissues were excised. Malondialdehyde (MDA) and glutathione (GSH) levels, and myeloperoxidase activity (MPO) were determined in the tissues, while oxidant-induced tissue fibrosis was determined using the collagen contents. Serum enzyme activities, cytokine levels, and leukocyte apoptosis were assayed in the plasma. In the AA group, GSH levels decreased significantly, while the MDA levels, MPO activity, and collagen content increased in the tissues suggesting oxidative organ damage. In the NAC + AA group, oxidant responses reversed significantly. Serum enzyme activities, cytokine levels, and leukocyte apoptosis, which increased following AA administration, decreased with NAC treatment. Therefore, supplementing with NAC can be useful when there is a risk of AA toxicity, as NAC inhibits neutrophil infiltration, balances the oxidant-antioxidant status, and regulates the generation of inflammatory mediators to protect tissues.
Keywords: Acrylamide; N-acetyl-L-cysteine; oxidative changes; collagen; myeloperoxidase; leukocyte apoptosis; TISSUE-DAMAGE; KAPPA-B; MYELOPEROXIDASE; APOPTOSIS; ACETYLCYSTEINE; GLUTATHIONE; CELLS